Teori Holland untuk Membantu Pemilihan Jurusan pada Siswa SMK - Ashfiya Nabila Arrasuli (Medan Resource Center, 2022)
Vocational High School is currently one of the school choices that are in great demand by the younger generation. The wide choice of skill programs offered by SMK is considered to be able to help the younger generation to master the skills that are needed as it is today so that it is hoped that SMK graduates can be directly absorbed by the industry. To assist students in determining the major to be followed, the school can conduct an assessment using the RIASEC test which was developed based on the theory of John Holland. This theory is considered comprehensive and relevant to assist students in choosing a major that suits their interests and aspirations.